2015
DOI: 10.1002/bdra.23371
|View full text |Cite
|
Sign up to set email alerts
|

Placenta previa and risk of major congenital malformations among singleton births in Finland

Abstract: Using a large population-based study, we found that placenta previa was weakly, but significantly associated with an increased risk of major congenital malformations in singleton births. Future studies should examine the association between placenta previa and individual types of congenital malformations, specifically in high-risk pregnancies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 28 publications
2
25
0
Order By: Relevance
“…Compared to controls, pregnancies with previa were significantly associated with preterm delivery prior to 28 weeks (3.5% vs. 1.3%; p = 0.003), 32 weeks (11.7% vs. 2.5%; p < 0.001), and 34 weeks (16.1% vs. 3.0%; p < 0.001) of gestation. Our study also agreed with Kancherla et al 6 who found that there was significant difference between gestational age in both groups with p value <0.001. Preterm with placenta previa may be explained by bleeding episodes leading to emergency cesarean section as well as elective cesarean sections contributes to the increased risk of preterm delivery with placenta Previa.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Compared to controls, pregnancies with previa were significantly associated with preterm delivery prior to 28 weeks (3.5% vs. 1.3%; p = 0.003), 32 weeks (11.7% vs. 2.5%; p < 0.001), and 34 weeks (16.1% vs. 3.0%; p < 0.001) of gestation. Our study also agreed with Kancherla et al 6 who found that there was significant difference between gestational age in both groups with p value <0.001. Preterm with placenta previa may be explained by bleeding episodes leading to emergency cesarean section as well as elective cesarean sections contributes to the increased risk of preterm delivery with placenta Previa.…”
Section: Discussionsupporting
confidence: 93%
“…In women without placenta previa age ranged from (16 -47) with mean±SD (29.59 ± 5.92) and in women with placenta previa age ranged from (17 -46) with mean±SD (31.75 ± 5.04), parity in women without placenta previa ranged from(0.0 -11) with median 2.0 (1 -3) while parity in women with placenta previa ranged from(0.0 -8) with median 3.0 (2 -3), in comparison according to Previous CS women without placenta previa who undergone CS ranged from(0.00 -7) with median 1 and with placenta previa with median2.00 (1 -3). There was highly statistically significant difference between both groups with p value< 0.001and this study agree with Kancherla et al 6 which was a retrospective populationbased study of all singleton births born at or after 22weeks of gestation in Finland during 2000 to 2010 who found that 49% of women had no placenta previa with ages more than 29 years while 57.2 % of them had placenta previa with p value< 0.001 and placenta previa increase in women with previous CS with percentage of 17.2 % in comparison to 10.5 in women without placenta previa with p value < 0.001 and there was no significant difference in parity in both groups.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This is smaller than what is reported by Kancher et al, 2015 who found 6.2% of women with PP delivered a singleton infant with a major congenital malformation, compared with 3.8% of unaffected women. 25 This is may be due to the sample size that was insufficient to detect the actual rates of congenital anomalies in these patients.…”
Section: Discussionmentioning
confidence: 97%
“…6,7 Placenta previa also was weakly but significantly associated with an increased risk of major congenital anomalies. 8 The current study aims to evaluate the prevalence of cases of PP and PA attending to Women's Health Hospital Assiut University in the period from January 2015 to December 2016. Additionally, to evaluate the maternal and neonatal outcomes of PP and PA.…”
mentioning
confidence: 99%